Decadal analysis of hydrography and in situ nutrient budgets in the western and eastern North Atlantic subtropical gyre - Cianca, Andrés; Helmke, Peer; Mouriño, Beatriz; Rueda, María José; Llinás Gonzalez, Octavio; Neuer, Susanne (Journal of Geophysical Research: Oceans, 2007)
The current debate about the mechanisms and magnitude of new nutrient input to the euphotic zone in subtropical gyres calls for studies which consider large and mesoscale perspectives by combining in situ time series and remote observations. We carried out a first of its kind comparative analysis of hydrography and sea level anomaly (SLA) at the oligotrophic time series stations BATS (Bermuda Atlantic Time Series Study) and ESTOC (European Station for Time Series, Canary Islands) using concomitant 10‐yr in situ and satellite altimetry data. The stations are located at about the same latitude in the western and eastern boundaries of the subtropical North Atlantic gyre, respectively, and provide the opportunity to study differences that may exist between both regions. Observed SLA was 0.25 m at BATS, compared with 0.12 m at ESTOC, a consequence of the higher eddy kinetic energy in the western compared with the eastern subtropical gyre. We quantified a detailed in situ nutrient budget for both time series stations; ESTOC received about 75% of the nutrients available for new production at BATS (in average 0.28 mol N m−2 yr−1 compared with 0.38 mol N m−2 yr−1, respectively), but the difference was not significant. However, significant differences in input mechanisms existed between both stations; eddy pumping constituted the main new nutrient source BATS, whereas wintertime convection was the main nutrient supply mechanism at ESTOC. In addition, the nutricline was significantly shallower at ESTOC compared with BATS, partly compensating for shallower mixed‐layer depths and SLA variability at the western station. We found considerable interannual variability in both eddy pumping and wintertime convection which may be related to NAO‐induced changes in the pattern of the subtropical gyre. 2,953 Q1